Advances on Analysis and Control of Vibrations Theory and Applications - Zapateiro de la Hoz, Mauricio; Pozo, Francesc (IntechOpen, 2012)
Vibration is a phenomenon that we can perceive in many systems. Their effects are as diverse as the personal discomfort that can produce the unevenness of a road or the collapse of a building or a bridge during an earthquake. This book is a compendium of research works on vibration analysis and control. It goes through new methodologies that help us understand and mitigate this phenomenon. This book is divided into two sections. The first one is devoted to new advances on vibration analysis while the second part is a series of case studies that illustrate novel techniques on vibration control. The applications are varied and include areas such as vehicle suspension systems, wind turbines and civil engineering structures.